Adaptive System for Streetlights in the Shopping Center Area of Purwakarta Region using Fuzzy Logic Method - Hadi Putri, Dewi Indriati; Pratama, Hafiyyan Putra; Venica, Liptia; Merdeka, Vormes Gema; Kautsar, Makna A'raaf (Universitas Sebelas Maret (UNS), 2023)
Streetlight systems generally use time condition as the parameter, which set the lights to be always on during specified period. This way, the system has flaws in its inefficiency and ineffectiveness. The system designed in this research considers the intensity of surrounding lights and passing pedestrians as the parameters, and fuzzy logic to get fuzzier output of the luminosity level for the streetlight. From the results of testing and analysis, it can be concluded that the design in this research has been successfully built as the results obtained are in accordance with the previously set fuzzy logic universe of discourse. By implementing an adaptive street lighting system in this study can help streamline light energy, because the street lighting lights can adjust themselves depending on the presence or absence of pedestrians passing by using a PIR sensor and the level of light brightness in that place using an LDR sensor.